'On water synthesis' of oxindoles bearing quaternary carbon center through C–H (sp3) functionalization of methyl azaarenes. Issue 5 (3rd February 2016) - Yaragorla, Srinivasarao; Singh, Garima; Dada, Ravikrishna
Graphical abstract: Abstract: A catalyst-free and green approach of sp 3 C–H functionalization of methyl azaarenes with malononitrile and isatins for the synthesis of oxindole derivatives bearing quaternary carbon center has been described in water. This one-pot three component synthesis endures the key features like first 'on water synthesis', short reaction times, moderate to good yields, and large substrate scope.